Pelaksanaan Pemenuhan Hak-Hak Narapidana Di Rutan Kelas IIB Demak - Indra Yuri Pradana; Edi Pranoto (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This research aims to analyze and evaluate the implementation of fulfilling prisoners' rights at the Class IIB Demak Detention Center. Fulfilling prisoners' rights is an important aspect in the criminal justice system which focuses on rehabilitation and social reintegration. This research uses a qualitative approach with data collection techniques through observation, interviews and documentation studies. The results of the research show that the implementation of fulfilling the rights of prisoners at the Class IIB Demak Detention Center experiences a number of challenges. Some rights, such as the right to health facilities, education and work, have not been fully fulfilled optimally. Limited facilities and infrastructure, a lack of manpower, and internal regulations that do not fully support the fulfillment of prisoners' rights are the main factors for deviations. However, this research also identified several good practices in fulfilling prisoners' rights, such as the existence of rehabilitation programs that focus on skills development and education. Collaborative efforts between internal and external parties are also recognized as a positive step in improving the living conditions of prisoners. Based on these findings, this research recommends improvements in the management of facilities and infrastructure, increasing the number of workers, as well as improving internal regulations to optimally support the fulfillment of prisoners' rights at the Demak Class IIB Detention Center. It is hoped that the results of this research can contribute to improving the system of detention and rehabilitation of prisoners in Indonesia in general.